Transplantation of neural stem cells improves recovery of stroke-affected mice and induces cell-specific changes in GSDMD and MLKL expression - Lisjak, Damir; Alić, Ivan; Šimunić, Iva; Mitrečić, Dinko (Frontiers in Molecular Neuroscience, 2024)
IntroductionStroke, the second leading cause of death and disability in Europe, is primarily caused by interrupted blood supply, leading to ischemia–reperfusion (IR) injury and subsequent neuronal death. Current treatment options are limited, highlighting the need for novel therapies. Neural stem cells (NSCs) have shown promise in treating various neurological disorders, including stroke. However, the underlying mechanisms of NSC-mediated recovery remain unclear.MethodsEighty C57Bl/6–Tyrc-Brd mice underwent ischemic stroke induction and were divided into four groups: sham, stroke-affected, stroke-affected with basal cell medium injection, and stroke-affected with NSCs transplantation. NSCs, isolated from mouse embryos, were stereotaxically transplanted into the stroke-affected brains. Magnetic resonance imaging (MRI) and neurological scoring were used to assess recovery. Immunohistochemical analysis and gene expression assays were performed to evaluate pyroptosis and necroptosis markers.ResultsNSC transplantation significantly improved neurological recovery compared to control groups. In addition, although not statistically significant, NSCs reduced stroke volume. Immunohistochemical analysis revealed upregulation of Gasdermin D (GSDMD) expression post-stroke, predominantly in microglia and astrocytes. However, NSC transplantation led to a reduction in GSDMD signal intensity in astrocytes, suggesting an effect of NSCs on GSDMD activity. Furthermore, NSCs downregulated Mixed Lineage Kinase Domain-Like Protein (Mlkl) expression, indicating a reduction in necroptosis. Immunohistochemistry demonstrated decreased phosphorylated MLKL (pMLKL) signal intensity in neurons while stayed the same in astrocytes following NSC transplantation, along with increased distribution in microglia.DiscussionNSC transplantation holds therapeutic potential in stroke recovery by targeting pyroptosis and necroptosis pathways. These findings shed light on the mechanisms underlying NSC-mediated neuroprotection and support their further exploration as a promising therapy for stroke patients.